2021
DOI: 10.1021/acs.jpcc.1c07617
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Anchoring and Diffusion for Screening of Metal Oxide Cathode Materials in Lithium–Sulfur Batteries

Abstract: Unfavorable factors such as the shuttle effect caused by soluble lithium polysulfides, insulation of S and Li 2 S, and large volume expansion of S have greatly hindered the practical application of lithium−sulfur batteries. Using sulfur cathodes based on metal oxide nanocomposite materials has been proven to be an effective method to overcome the abovementioned problems and accomplish longterm cycle stability, excellent conductivity, and high-rate capacity. However, there is still a lack of clear mechanism res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The following reduction steps, from Li 2 S 8 to Li 2 S, are almost all endothermic. The previous researches showed that the step with the largest positive Gibbs free energy barrier (Δ G barrier ) is the most difficult step for SRR in Li–S batteries. , According to the calculated equation of Δ G , , the Δ G barrier of SRR varies significantly depending on the difference in anchoring ability to Li 2 S n . Such as LiPSs adsorbed on Cr 2 CO 2 , Li 2 S 8 has the strongest adsorption energy, while Li 2 S 6 has a relatively weak interaction energy, resulting in a high barrier for Li 2 S 8 → Li 2 S 6 (1.338 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The following reduction steps, from Li 2 S 8 to Li 2 S, are almost all endothermic. The previous researches showed that the step with the largest positive Gibbs free energy barrier (Δ G barrier ) is the most difficult step for SRR in Li–S batteries. , According to the calculated equation of Δ G , , the Δ G barrier of SRR varies significantly depending on the difference in anchoring ability to Li 2 S n . Such as LiPSs adsorbed on Cr 2 CO 2 , Li 2 S 8 has the strongest adsorption energy, while Li 2 S 6 has a relatively weak interaction energy, resulting in a high barrier for Li 2 S 8 → Li 2 S 6 (1.338 eV).…”
Section: Resultsmentioning
confidence: 99%